A new Drusinae (Trichoptera: Limnephilidae) species from the Zagros Mountains in the Kurdistan Province, Iran - Ibrahimi, Halil; Mohammadi, Habibollah; Ghaderi, Edris; Karimian, Erfan (Zootaxa, 2024)
A new species of the Drusinae subfamily, Drusus chelchamaensis Ibrahimi & Mohammadi sp. nov., is described based on male genital morphology. The male of the new species is most similar to that of Drusus bayburtii Çakin 1983 (known from several places in Anatolia, Turkey), Drusus ketes Oláh & Mey 2017 (in Oláh et al. 2017) (known from the Hamedan Province, Iran), and Drusus kazanciae Çakin 1983 (known from the Hakkari Province, Turkey) and differs in the formation of superior appendages, intermediate appendages, inferior appendages, parameres, spinate area of segment VIII, and segment IX. The species is currently known only from Chel Chama Mountain in the Kurdistan Province of Iran and is the second known species of the Drusus caucasicus Species Complex from Iran. Chel Chama is part of the Zagros Mountains, which is rich in freshwater ecosystems, but currently with only a few reported species of caddisflies.